Investigation of the Protective Effects of Phlorizin on Diabetic Cardiomyopathy in db/db Mice by Quantitative Proteomics - Qian Cai; Baoying Li; Fei Yu; Weida Lu; Zhen Zhang; Mei Yin; Haiqing Gao (Journal of Diabetes Research)
Patients with diabetes often develop hypertension and atherosclerosis leading to cardiovascular disease. However, some diabetic patients develop heart failure without hypertension and coronary artery disease, a process termed diabetic cardiomyopathy. Phlorizin has been reported to be effective as an antioxidant in treating diabetes mellitus, but little is known about its cardioprotective effects on diabetic cardiomyopathy. In this study, we investigated the role of phlorizin in preventing diabetic cardiomyopathy in db/db mice. We found that phlorizin significantly decreased body weight gain and the levels of serum fasting blood glucose (FBG), triglycerides (TG), total cholesterol (TC), and advanced glycation end products (AGEs). Morphologic observations showed that normal myocardial structure was better preserved after phlorizin treatment. Using isobaric tag for relative and absolute quantitation (iTRAQ) proteomics, we identified differentially expressed proteins involved in cardiac lipid metabolism, mitochondrial function, and cardiomyopathy, suggesting that phlorizin may prevent the development of diabetic cardiomyopathy by regulating the expression of key proteins in these processes. We used ingenuity pathway analysis (IPA) to generate an interaction network to map the pathways containing these proteins. Our findings provide important information about the mechanism of diabetic cardiomyopathy and also suggest that phlorizin may be a novel therapeutic approach for the treatment of diabetic cardiomyopathy.